Menelisik Pengembangan Profesi Widyaiswara : Inovasi Paten - Slamet Yuswanto (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
This paper aims to find out the implementation of the provisions of Article 8 paragraph (4) letter d of the Minister of Administrative Reform and Bureaucratic Reform No. 22 of 2014 concerning Widyaiswara's Functional Position and Credit Numbers. The writing method uses normative-empirical legal research with a synchronization approach to several laws and regulations. Primary data were obtained from interviews with widyaiswara, while secondary data came from laws, government regulations and ministerial empowerment ministerial regulations. The research results obtained that the provisions of Widyaiswara's professional development through the discovery of patented innovations and who have been included in the list of patents in accordance with their specialized fields of expertise, cannot be implemented by Widyaiswara.